Local Power Dynamics and Procurement Politics in Bima-Dompu: Uncovering Embedded Structural Corruption - Nurlaila (KOMUNITAS, 2025)
This study uncovers the latent structure of systemic corruption in public procurement across Bima City, Bima Regency, and Dompu Regency, revealing a pathological convergence of state capture, neopatrimonialism, and crony capitalism. Using a critical qualitative approach with an intrinsic case study design, it integrates Foucault’s governmentality, institutional corruption theory, and Baudrillard’s simulacra to explain how procurement mechanisms shift from administrative instruments into tools of predatory power consolidation. Data were obtained through elite interviews, legal and audit document analysis, and participatory observation, and analyzed using critical discourse analysis within abductive reasoning. The findings show procurement systems hijacked through orchestrated collusion, fabricated documentation, and bureaucratic manipulation under pseudo-legality. The research concludes that procurement corruption has become an institutionalized governing regime that erodes democratic legitimacy, degrades bureaucratic ethics, and endangers the sustainability of local public governance.